Abundance, biomass and functional structure of the saprophagous macrofauna in the litter and soil of Mediterranean oak forests (PEDOBIOLOGIA, 1999)
The saprophagous macrofauna (macroarthropods, gastropods, earthworms) was sampled in five Mediterranean forests of southern France: two helm oak (Quercus ilex) sites on limestone, two downy oak (Q. pubescens) sites on limestone and a helm oak site on schist. The total biomass was high, ranging from 52.1 to 113.1 g fresh mass m(-2). Classification of species into functional groups (epigeic, epi-anecic, anecic and endogeic) showed that the four groups were well represented in this region. However, the density and biomass of epigeic macroarthropods (mainly millipedes) were significantly higher at the helm oak sites on limestone (186 ind. m(-2); 9.6 g m(-2)) than at the other sites. In contrast, the density and biomass of epi-anecic earthworms (Lumbricus spp.) were higher at the downy oak: sites on limestone (13 ind. m(-2); 16.7 g m(-2)). Anecic earthworms (Aporrectodea and Scherotheca spp.) were dominant in terms of biomass at all sites (overall mean 56.6 g m(-2)). Although the results are consistent with possible competitive interactions between epigeic macroarthropods and epi-anecic earthworms, they also show a high degree of coexistence between both of these groups and anecic earthworms. The study provides an insight into the possible responses of the macrofauna of N-W Europe to climate change towards warmer and drier conditions. There is potential for maintenance of all the functional groups that take part in the formation of forest mull.